Luces de la ciudad - Chaplin, Charlie, 1889-1977; Cherrill, Virginia, 1908-1996; Garcia, Allan, 1887-1938; Lee, Florence, 1888-1962; Mann, Hank, 1887-1971; Myers, Harry, 1886-1938; Pollock, Gordon, m. 1956; Totheroh, Roland H., 1890-1967 (MK2 Editions : Distributed by Warner Home Video, 2003)
A tramp wins the love of a blind flower girl and attempts to obtain money from a millionaire to help her regain her sight.